2015
DOI: 10.1002/tia2.20026
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Pedagogical Solitude: The Transformative Power of Discipline-Specific Faculty Learning Communities

Abstract: This article describes a multiyear Faculty Learning Community (FLC) program as a strategy to overcome pedagogical solitude (Shulman, 1993) in a discipline‐specific context. Participant interviews shed light on their FLC experiences and perceived impact on their teaching and students’ learning. Grounded within the particularities of the disciplinary context and based on the results of interviews reflecting a highly positive experience, key factors that had a major role in the success of the FLCs are articulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Faculty learning communities (FLCs), which are small groups of faculty who meet regularly over an extended period of time with the objective of improving their teaching ( Cox, 2004 ), are also designed to take advantage of collegial support. FLC participants have reported that the experience helps them change their teaching, for instance, by building their confidence in experimenting with different teaching strategies ( Tovar et al. , 2015 ) and promoting use of student-centered teaching practices ( Polich, 2008 ; Light et al.…”
Section: Introductionmentioning
confidence: 99%
“…Faculty learning communities (FLCs), which are small groups of faculty who meet regularly over an extended period of time with the objective of improving their teaching ( Cox, 2004 ), are also designed to take advantage of collegial support. FLC participants have reported that the experience helps them change their teaching, for instance, by building their confidence in experimenting with different teaching strategies ( Tovar et al. , 2015 ) and promoting use of student-centered teaching practices ( Polich, 2008 ; Light et al.…”
Section: Introductionmentioning
confidence: 99%
“…Returning to FLCs, since 2004, the topic has received little attention. Past scholarship has examined cross-disciplinary faculty communities (Hubball & Albon, 2007) and discipline-specific faculty learning communities (Addis et al, 2013;Tovar, Jukier, Ferris, & Cardoso, 2015) yet additional studies are necessary in order to confirm the effectiveness of and motivations behind faculty learning communities (Glowacki-dudka & Brown, 2007;Hubball & Albon, 2007).…”
Section: Faculty Learning Community (Flc)mentioning
confidence: 99%
“…FLCs are a transformative practice in which faculty participate in groups of usually between six and 15 members, to generate an actionable goal or product [10], [11], [12]. They are based on the premise that universities are places of learning for all, including faculty, and can be a way to foster collaboration [12].…”
Section: Flc Formation and Activitiesmentioning
confidence: 99%
“…FLCs are a transformative practice in which faculty participate in groups of usually between six and 15 members, to generate an actionable goal or product [10], [11], [12]. They are based on the premise that universities are places of learning for all, including faculty, and can be a way to foster collaboration [12]. FLCs have been demonstrated as valuable for cross-campus collaborations [12], [13], faculty development [14], curriculum development [15], generating teaching resources [16], and scholarship of teaching and learning [14], [17], [18].…”
Section: Flc Formation and Activitiesmentioning
confidence: 99%
See 1 more Smart Citation